Dupilumab: Direct Cost and Clinical Evaluation in Patients with Atopic Dermatitis - Marco Ferrari; Matthew G. Donadu; Gabriele Biondi; Laura Saderi; Federica Sucato; Maria A. Montesu; Paola Ruggiu; Paola Merella; Carla Chessa; Angela Sias; Gabriella Carmelita; Vittorio Mazzarello; et al. (Dermatology Research and Practice)
Health care spending in Italy is high and continues to increase; assessing the long-term health and economic outcomes of new therapies is essential. Atopic dermatitis (AD) is a chronic, pruritic, immune-mediated inflammatory dermatosis, a clinical condition that significantly affects patients’ quality of life at a high cost and requires continuous care. This retrospective study aimed to assess the direct cost and adverse drug reactions (ADRs) of Dupilumab and patients’ clinical outcomes. All AD patients treated with Dupilumab at the Sassari University Hospital, Italy, between January 2019 and December 2021 were included. Eczema Area Severity Index, Dermatology Life Quality Index, and Itch Numeric Rating Scale scores were measured. ADRs and drug expenses were analyzed. A statistically significant posttreatment improvement was observed for all the indices measured: EASI (P<0.0001), DLQI (P<0.0001), NRS (P<0.0001). The total expenditure for Dupilumab, in the observed period, amounted to € 589.748,66 for 1358 doses, and a positive correlation was shown between annual expenditure and delta percentage of variation pre- and posttreatment for the clinical parameters evaluated.